Extrapyramidal Signs and Risk of Progression from Mild Cognitive Impairment to Dementia: A Clinical Research Center for Dementia of South Korea Study - Myung, Woojae; Park, Jin Hong; Woo, Sook-Young; Kim, Seonwoo; Kim, Sang Ha; Chung, Jae Won; Kang, Hyo Shin; Lim, Shinn-Won; Choi, Junbae; Kim, Seong Yoon; Lee, Jae-Hong; Han, Seol-Heui; et al. (Psychiatry investigation, 2017)
Extrapyramidal signs (EPS) are common in patients with mild cognitive impairment (MCI). However, few studies have assessed the effect of EPS on the clinical course of MCI. We aimed to evaluate whether patients with EPS show more frequent progression from MCI to Alzheimer's disease (AD) and to other types of dementia. Participants (n=882) with MCI were recruited, and were followed for up to 5 years. The EPS positive group was defined by the presence of at least one EPS based on a focused neurologic examination at baseline. A total of 234 converted to dementia during the follow-up period. The risk of progression to AD was lower in the patients with EPS after adjusting for potential confounders [hazard ratio (HR)=0.70, 95% confidence interval (CI)=0.53-0.93, p=0.01]. In contrast, the patients with EPS had a six-fold elevated risk of progression to dementia other than AD (HR=6.33, 95%CI=2.30-17.39, p<0.001). EPS in patients with MCI is a strong risk factor for progression of MCI to non-Alzheimer dementia. The careful neurologic examination for EPS in patients with MCI can yield important clinical information for prognosis.